Lack of family education in boarding primary schools in China's minority areas: A case study of Stone Moon Primary School, Nujiang Lisu Autonomous Prefecture - Guo, Guo; Chen, Yao (Frontiers in Psychology, 2023)
The lack of family education in boarding primary schools in ethnic minority areas negatively impacts students' physical and mental health. This study constructed an analytical framework for the lack of family education in boarding primary schools from the perspective of Overlapping Spheres of Influence theory. Taking Stone Moon Primary School of Lisu people in Nujiang Prefecture as a field site, the study found that the lack of family education in boarding primary schools in ethnic areas primarily reflects the absence of family education content, the absence of family education emotion, and the Space-Time migration of family education. “Teachers' avoidance of educational risks”, “the weakening of family education under the background of flourishing schooling”, and “the capacity limit of policies and regulations” positively correlate with the lack of family education in boarding primary schools in ethnic minority areas. Possible solutions include establishing a responsibility standard system and accountability system between teachers and parents, and strengthening the compensation management of family education function in boarding primary schools in ethnic minority areas.